Application of Bayesian modelling to assess food quality & safety status and identify risky food in China market. (June 2019) - Yang, Yongheng; Wei, Lijuan; Pei, Jianan
Abstract: Lack of reliable information on quality & safety status in China Market, associated with food quality & safety scandals in the past years, would increase consumers' concerns with and anxieties about the quality and/or safety of food they purchased or may purchase. In this study, Bayesian modelling was combined with a meta-analysis technique to assess the overall food quality & safety status and identify risky food in China market. Results indicated that 98.26% (95% CI of 98.21%–98.31) of food products in China market were meeting related food quality & safety standards; dairy products and food additives exhibited lowest quality & safety risk; beverages, alcohols, processed fruit/vegetable products, and catering food were included in the 3 categories which were identified as risky food. The methods in this study could be used as useful tools for public administrations to assess quality & safety status of food products in market, and also for food producers to evaluate quality & safety levels of their products. Highlights: Overall qualification rate of food products in China market was 98.26%. Dairy products and food additives were of lowest food quality & safety risk. Three categories were identified as risky food.